Host security threat analysis approach for network dynamic defense - Lixun LI; Bin ZHANG; Shuqin DONG (网络与信息安全学报)
Calculating the host security threat in network dynamic defense (NDD) situation has to consider the vulnerabilities’ uncertainty because of dynamic mutation.Firstly,the vulnerabilities’ uncertainty caused by the mutation space and the mutation period was calculated by random sampling model,and combined with the CVSS,the attack success probability formula of single vulnerability was derived.Secondly,to avoid self-loop during the path searching process in multiple vulnerabilities situation,an improved recursive depth first algorithm which combined with node visited queue was proposed.Then,the host security threat was calculated based on attack success probability in the situation of multiple vulnerabilities and paths.Finally,approach’s availability and effectiveness were verified by an experiment conducted in a typical NDD situation.